Análise da convencionalidade e constitucionalidade da política de cotas para mulheres enquanto medida válida para combater a discriminação de gênero nas relações de trabalho - Barbosa, Luiza Fernandes de Abrantes (2023)
Gender discrimination in labor relations is a social problem that violates equal dignity and makes it impossible to implement decent work due to the devaluation of female work in contrast to male work. This discrimination can be observed from the selection process, salary difference, suffering from harassment and especially in promotion/ascension of career in the labor market. It so happens that the mere existence of norms about equality and non-discrimination are not enough to eradicate this reality, which is why it is necessary to adopt affirmative actions, in particular the quota policy, as an apt means of effecting social transformation. That said, the following question arises: is the policy of quotas for women in the labor market a legally valid measure to combat gender discrimination within the scope of International Human Rights and Labor Law and Brazilian Constitutional Law? The hypothesis of the constitutionality and conventionality of this measure is raised to increase female representation in positions of power and command of large companies. In this sense, this dissertation seeks to investigate the question of the legal validity of the policy of quotas for women based on the norms of equality and non-discrimination. Therefore, it is necessary to achieve these specific objectives: contextualize gender discrimination in the Brazilian labor market, discuss the system of protection of International Human Rights Law, Inter-American Law and International Labor Law in the fight against discrimination in labor relations; evaluate the international and national experience in relation to the quota policy and examine the legal validity of the quota policy for women in the labor market in the light of conventionality and constitutionality controls. This study has an applied nature and a qualitative approach. The procedural techniques adopted were bibliographical research and the analysis of international and national regulations, bills and regulations arising from Comparative Law. The preparation of this work is justified by the fact that the theme is current and has a direct relationship with the promotion of gender equality, which is one of the Goals for Sustainable Development. With regard to the results, it was found that the policy of quotas for women in management/leadership positions is a valid measure to combat gender discrimination in labor relations, as well as being reasonable and proportionate to remedy a structural problem such as the gender discrimination.